Judicial Review “Satu Atap” Peraturan Perundang-Undangan di Bawah Kewenangan Mahkamah Konstitusi - Yunaldi, Wendra (Pagaruyuang Law Journal, 2018)
The constitutional dual judicial review of the Constitutional Court and the regulation in the Supreme Court has created legal uncertainty in the legal system of Indonesia. The application of graded judicial review has a negative impact on the guarantee of the constitutional rights of the community. The hierarchical model of the prevailing law-enforcement regulation is the abandonment of the legal norms of the constitution in every level of legal product downward. Disconnection of constitutional norms only up to the level of the Act will be a denial of the rights of the people of Indonesia at all levels of statutory legislation under the law. As a rule of law, legal products have a value of truth and justice that refers to the source of the main legal order, namely the Constitution, so that Indonesia's constitutionalism can be tiered up and down down. Thus, there is no differentiation of the "legal certainty" between the 1945 Constitution and the KMPR, as well as the Act as an implementation product with various derivatives such as the Perpu, PP, Perpres, Provincial Regulations and Regency / City Regulations. The general nature of the constitutional arrangements becomes the standard of truth so that every act of government can be controlled and evaluated by the constitution. This situation is different from what is happening now, where the justice of regulation embodied by the Supreme Court is often biased toward the interests of "securing" the contents of the regulation rather than granting legal justice rights, not to mention the long waiting periods of unclear ends. MA finally failed to bring about legal justice for the community. This is where judicial review or judicial constitutional should be placed on the shoulders of the Constitutional Court so that the conception of the Indonesian legal state not only applies only at the national level, but also becomes a backbone for the community in each region through the granting of the right of the people to obtain justice through the examination of legal products that harm the constitutional rights community.